Aspects of physicians' attitudes towards the rational use of drugs at a training and research hospital: a survey study - AKICI, AHMET (SPRINGER HEIDELBERG, 2013)
The rational use of drugs (RUD) is primarily the responsibility of physicians. The aim of this study was to investigate whether physicians are aware of RUD principles and how they apply them in daily medical practice. A total 136 physicians working at the Kartal Training and Research Hospital in Istanbul were enrolled in the study between February and March 2012. A face-to-face interview was conducted with physicians to assess their knowledge and attitude regarding RUD. A large majority of the physicians declared that consultation time was insufficient (84 %). The data obtained from the survey indicate that 54 % of the enrolled physicians monitored the therapeutic outcome and that 27 % found the information given to the patient to be sufficient. Participating physicians stated that the less known characteristics of the drugs they prescribed were drug interactions, traceability in market, and price. The most preferred reference source was Vademecum (a drug guideline prepared by the private sector). Two major factors contributing to prescribing patterns were self study and observation of teachers at clinical training. There was a significant difference between internists-surgeons and residents-specialists in the number of prescribed drugs per prescription (p < 0.001) and in the information provided to the patient on the prescribed drugs (name, effect, dose, instructions, possible side effect) (p < 0.05), respectively. Our findings overall show that the principles of RUD were not fully applied in daily medical practice by the participating physicians. One important reason for this is a heavy patient load, which requires a change in managerial practices within the healthcare system. The other, more essential explanation is education; consequently, serious consideration should be given to including effective clinical pharmacotherapy training and RUD courses in the medical education curriculum.
Keywords: Rational use of drugs; Pharmacotherapy training; Physicians; Medical information; UNDERGRADUATE MEDICAL-STUDENTS; CLINICAL-PHARMACOLOGY; GENERAL-PRACTITIONERS; PHARMACOTHERAPY; THERAPEUTICS; IMPACT; PRESCRIPTION; COMPETENCE